Investigation of level and differentials in child mortality in South Africa: insight from Census 2001 and 2011, Community Survey 2016 and Demographic and Health Survey 2016 - Matikinca, Ntombizandile (Centre for Actuarial Research (CARE), 2023)
Measuring levels of childhood mortality is important for low and middle-income countries to monitor overall development and progress towards improved child health. The overall aim of this research is to estimate the level and trend of childhood mortality in South Africa over time, and to examine the factors associated with and the determinants of childhood mortality. The study discovered that significant progress has been made to reduce the levels of childhood mortality in the country. The estimates derived through direct estimation using the 2016 South African Demographic and Health Survey (SADHS) for the period between 2012-2016 revealed age-specific mortality rates were: Neonatal Mortality Rate (NMR) was 22.0 per 1 000 live births, Post-neonatal Mortality Rate (PNMR) 13.1, 1q0 34.9, 1q4 5.5 and 5q0 40.2 per 1 000 live births. Investigation of the factors associated with childhood mortality revealed significant differentials in age group, sex, population group, province, socio-economic status and household characteristics. Overall, children aged less than one month and those aged between one to two months had a higher mortality risk than the other age groups; male children had an increased risk of dying than females; Black and Coloured children had an increased risk of dying compared to children in other population groups; children in Mpumalanga, Eastern Cape and North West had a higher risk of dying compared to children in other provinces; children whose mothers had below secondary education had higher risks of mortality; and children with poor water source and toilet facility were more likely to die than other children with better facilities. The results were generally in agreement with the existing literature. Although the study found significant improvement in the level of childhood mortality over the period 1996-2016, further progress is achievable as many children still continue to die of preventable or treatable causes. The findings of this study may assist government, policymakers and researchers to plan, and implement targeted interventions that will further reduce the levels of childhood mortality in South Africa.